An Embedded fuzzy type-2 controller based sensor behavior for mobile robot - Siti Nurmaini, 1969-, author; Siti Zaiton Mohd. Hashim, author; International Conference on Intelligent Systems Design and Applications (8th: 2008: Taiwan) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL